2009
DOI: 10.1002/ange.200901607
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2‐oxazoline): eine Polymerklasse mit vielfältigen Anwendungsmöglichkeiten

Abstract: Die lebende kationische Ringöffnungspolymerisation von 2‐Oxazolinen ist seit ihrer Entdeckung 1966 eingehend untersucht worden. Die Vielseitigkeit der lebenden Polymerisation ermöglicht die Copolymerisation verschiedener 2‐Oxazolin‐Monomere zu Polymeren mit einstellbaren Eigenschaften; so lassen sich z. B. hydrophile, hydrophobe, fluorophile sowie harte und weiche Materialien erhalten. Allerdings geriet diese Polymerklasse wegen der langen Reaktionszeiten und ihrer beschränkten Anwendungsmöglichkeiten in den 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 196 publications
(229 reference statements)
0
8
0
1
Order By: Relevance
“…The association and dissociation at the UCST is observed to Figure S3.3 in the Supporting Information). Whilst LCST behavior has been observed in many thermoresponsive synthetic polymers [1,5] and proteins including EMPs, [2,6] UCST behavior is not common. UCST behavior has been reported in complex multisystem interpenetrating networks [18] of poly(acrylamide) and poly(acrylic acid), polyzwitterions, [19] and in gelatin.…”
Section: Dedicated To Professor John Ralston On the Occasion Of His 6mentioning
confidence: 96%
See 1 more Smart Citation
“…The association and dissociation at the UCST is observed to Figure S3.3 in the Supporting Information). Whilst LCST behavior has been observed in many thermoresponsive synthetic polymers [1,5] and proteins including EMPs, [2,6] UCST behavior is not common. UCST behavior has been reported in complex multisystem interpenetrating networks [18] of poly(acrylamide) and poly(acrylic acid), polyzwitterions, [19] and in gelatin.…”
Section: Dedicated To Professor John Ralston On the Occasion Of His 6mentioning
confidence: 96%
“…[1][2][3][4][5] At present these materials are prepared from a limited number of synthetic polymers, biopolymers, and biomimetic polymers. Protein engineering approaches to biomaterials design offer powerful strategies to overcome challenges and provide new opportunities in the design and rapid development of responsive biomaterials.…”
Section: Dedicated To Professor John Ralston On the Occasion Of His 6mentioning
confidence: 99%
“…Nonetheless, the application of poly(2‐oxazoline)s in biomedical fields arose only recently, and although both types of polymers have been quite widely tested for different drug‐carrier applications, only a few basic biological and stability studies have been reported 148. 149 Drug‐transport systems with poly(2‐oxazoline) were developed, for example, based on micelles of PLA‐PEtOx‐PLA [PLA=poly(lactic acid)] as carriers of doxorubicin 150. PEtOx‐poly(ε‐caprolactone) micelles with paclitaxel have been shown to possess the same efficiency as Cremophor EL formulated paclitaxel 151.…”
Section: Potential Alternatives To Pegmentioning
confidence: 99%
“…Bio‐ and hemocompatibility in vitro and in vivo were found to be in the range of PEG 252. Poly(2‐methyl‐2‐oxazoline) and poly(2‐ethyl‐2‐oxazoline) also demonstrated effects similar to PEG with regard to blood half‐life, opsonisation, and organ distribution 253. However, systematic investigations of toxicological and immunological effects are still missing.…”
Section: The Future Has Already Begunmentioning
confidence: 99%